Criminal Liability for Corruption and Constitutional Responsibility of the State in the Whoosh High-Speed Rail Megaproject Case: Analysis of Mark-ups, Debt, and Restructuring - Farman, Eka; Syahrul; Damianus Wanda Ndapa; Hazairin; Musmuliadin; Syamsuddin (Yayasan Cahaya Generasi Positif, 2025)
This study examines criminal liability for corruption and the constitutional responsibility of the state regarding the Jakarta-Bandung High-Speed Railway Project (Whoosh), analyzing budget mark-ups, state-owned enterprise debt, and financial restructuring. The Whoosh project, classified as a National Strategic Project, has experienced significant cost overruns that raised serious governance concerns. Construction costs reached approximately USD 52 million per kilometer, three times higher than comparable projects in China (USD 17-18 million per kilometer), suggesting potential criminal corruption through budget inflation in the Estimated Price (HPS) determination. Concurrently, the financial crisis at PT Kereta Cepat Indonesia China (KCIC) and its parent company, PT Kereta Api Indonesia (KAI), necessitated State Capital Participation (PMN) injections from the national budget, creating constitutional burden on state finances. This research employs a normative-empirical legal methodology, integrating doctrinal analysis of Indonesian constitutional law, anti-corruption legislation, and state finance laws with empirical examination of KPK investigations and fiscal impacts. The study proposes a Dual Accountability model that integrates criminal and constitutional dimensions, linking alleged budget mark-ups causally to state losses and subsequent constitutional obligations. Findings indicate that corporate accountability through anti-corruption enforcement must operate simultaneously with constitutional oversight of state-owned enterprises, consistent with Constitutional Court Decision No. 14/PUU-XVI/2018. This integrated approach ensures comprehensive resolution requiring both penal recovery channels and constitutional safeguards before financial bailouts are approved. The research contributes to understanding how infrastructure megaproject failures implicate dual accountability mechanisms and informs governance reforms necessary for managing National Strategic Projects effectively.